Efektivitas Program Karantina 30 Hari dalam Menghafal Al-Qur’an 30 Juz di PP Miftahul Huda Wonosobo - Rifqi Muntaqo; Nely Fitriana (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This study aims to explain the concept and implementation of a 30-day quarantine program in memorizing Al-Qur'an 30 juz at the Miftahul Huda Islamic boarding school in Wonosobo. This research approach is qualitative, while the physical techniques of the data are; Win affairs, interviews and documentation. By analyzing data, students / students have enthusiasm and enthusiasm when learning memorization takes place, students / students are able to meet the target every day. Students / students are always disciplined and disciplined in activities, most students / students meet the target targets on time. This study concluded that the 30-day quarantine program at PP Miftahul Huda Siwatu Wonosobo can significantly fulfill the target of the 30-juz al-Qur'an memorization of the santri.